2019
DOI: 10.1200/jco.2019.37.7_suppl.18
|View full text |Cite
|
Sign up to set email alerts
|

GATA2 exosomal mRNA: A novel urine biomarker for the diagnosis of clinically significant prostate cancer.

Abstract: 18 Background: Prostate specific antigen (PSA) detection in blood is widely used to screen for prostate cancer (PCa). However, PSA has limited utility in discriminating tumors at high risk of progression from indolent-low risk tumors, which leads to PCa overtreatment and highlights the need to identify better biomarkers for the detection of clinically significant PCa (Gleason Score; GS ≥ 7). Here, we introduce a novel mRNA GATA2 exosomal biomarker detected in urine useful to diagnose clinically significant PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…With the protection of a membrane structure, exosomes effectively transfer various biomolecules such as nucleic acids, proteins, and lipids between cells for intercellular communication. , Recent evidence has indicated that exosomes participate in not only physiological regulations but also pathological processes of cancer, including tumorigenesis, angiogenesis, metastasis, and drug resistance; therefore, they have become promising biomarkers for cancer liquid biopsy. Among various cargos, exosomal RNAs, including both microRNAs (miRs) and mRNAs, have shown great diagnostic values in cancer. For example, a panel of exosomal miRNAs (let-7b, let-7e, miR-24, miR-21) from plasma detected non-small cell lung cancer (NSCLC) with an area under the curve (AUC) value as high as 0.899 . Exosomal GATA2 mRNA was found to be a predictive, urine-based biomarker for the diagnosis of clinically significant prostate cancer …”
Section: Introductionmentioning
confidence: 99%
“…With the protection of a membrane structure, exosomes effectively transfer various biomolecules such as nucleic acids, proteins, and lipids between cells for intercellular communication. , Recent evidence has indicated that exosomes participate in not only physiological regulations but also pathological processes of cancer, including tumorigenesis, angiogenesis, metastasis, and drug resistance; therefore, they have become promising biomarkers for cancer liquid biopsy. Among various cargos, exosomal RNAs, including both microRNAs (miRs) and mRNAs, have shown great diagnostic values in cancer. For example, a panel of exosomal miRNAs (let-7b, let-7e, miR-24, miR-21) from plasma detected non-small cell lung cancer (NSCLC) with an area under the curve (AUC) value as high as 0.899 . Exosomal GATA2 mRNA was found to be a predictive, urine-based biomarker for the diagnosis of clinically significant prostate cancer …”
Section: Introductionmentioning
confidence: 99%